A More Precise Modeling Method for Pneumatic Cabin Pressure Control System considering the Ambient Environmental Impacts - Yonggui Zheng; Meng Liu; Junjun Zhuang; Hao Wu (International Journal of Aerospace Engineering)
Pneumatic cabin pressure control system (PCPCS), with its exceptional electromagnetic compatibility, is expected to become the major equipment on a high-performance airplane again in the future. Although the PCPCS has been mature for a long time, the broad popularization of the digital cabin pressure control system (DCPCS) has left the PCPCS in the cold for decades. This makes the PCPCS unable to meet the severe cabin pressure regulation requirements of high-speed aircraft today. For this purpose, a more precise PCPCS modeling method is proposed. Through this method, the relation between different parts in the PCPCS can be accurately characterized. Moreover, the impact of the ambient environment on the PCPCS is taken into consideration. This method can be used to accurately analyze the PCPCS under maneuvering flight. And it also assists in the verification of the system improvements of dynamic performance in the future. Simulation results show that the aircraft acceleration disturbs the PCPCS slightly, and the cabin air inflow fluctuation has a significant impact on the cabin air pressure.